The Switch from the Forced Labour to the Hired Employment in the Coal Mining of Vorkuta City in 1950-60s: Changing of the Worker’s status. Interweaving of Social and Economic Aspects. - ДобряковаМария Сергеевна (Journal of Economic Sociology, 2010)
The paper investigates the transition from the forced labour to the hired employment in the coal mining of Vorkuta city in 1950-60s. The analysis is based on the theoretical approaches of social closure concept and social exclusion concept (Weber, Parkin); status crystallization (Lenski); embeddedness of economic relations in the social structures (Granovetter). It was shown how the closed from outside negatively privileged group of prisoners was changed by open positively privileged group of civilians. Data sources: archive materials of Siktivkar and Vorcuta cities.